The Influence of Learning Motivation and Class Climate on Character of Students Entrepreneurs in Vocational School Ekatama Pekanbaru - Rice, Nasoni Okta; Caska, Caska; Natuna, Daeng Ayub (International Journal of Economic, Business & Applications, 2019)
This study aims to determine the effect of learning motivation and class climate on students' entrepreneurial character. This research was conducted in Vocational School (SMK) Ekatama Pekanbaru. The population in this study were students of class X and class XI as many as 115 respondents by first passing an instrument test of 30 respondents. Data collection is done through a questionnaire. The method of analysis used is path analysis. The results in this study can be briefly explained as follows: 1) There is a significant influence between learning motivation on students' entrepreneurial character 2). There is a significant and positive influence between classroom climate on the entrepreneurial character of students, 3). Student climate and motivation to influence the character of entrepreneurship 4). There is an influence of student learning motivation through the classroom climate on entrepreneurial character. It can be concluded that the better the motivation to learn and the class climate, the better the entrepreneurial character of students at SMK Ekatama Pekanbaru.